The nature of π-hole interactions between iodide anions and quinoid rings in the crystalline state - Valentina Milašinović; Vedran Vuković; Anna Krawczuk; Krešimir Molčanov; Christoph Hennig; Michael Bodensteiner (IUCrJ, 2023)
The investigated co-crystal of 3-chloro-N-methylpyridinium iodide with tetrabromoquinone (3-Cl-N-MePy·I·Br4Q) reveals a π-hole interaction between an iodide anion and a quinoid ring involving an n → π* charge transfer. The quinoid ring has a partial negative charge (estimated to be in the range 0.08–0.11e) and a partial radical character, which is related to the black colour of the crystals (crystals of neutral tetrabromoquinone are yellow). A detailed X-ray charge density study revealed two symmetry-independent bond critical points between the iodide anions and carbon atoms of the ring. Their maximum electron density of 0.065 e Å−3 was reproduced by quantum chemical modelling. The energy of the interaction is estimated to be −11.16 kcal mol−1, which is comparable to the strength of moderate hydrogen bonding (about −10 kcal mol−1); it is dominantly electrostatic in nature, with a considerable dispersion component.